Количественный анализ задачи «Лев и Человек» при наличии кругового препятствия - Маматов, М.Ш.; Зуннунов, А.О.; Эсонов, Э.Э. (Проблемы управления и информатики, 2020)
Розглянуто задачу «Лев і Людина» в сенсі L-упіймання, тобто потрапляння в деяку околицю за наявності кругової перешкоди. Запропоновано структуру побудови кусково-постійних управлінь переслідування, яка забезпечує завершення гри за кінцевий час. Отримано оцінку зверху для завершення переслідування. In this work, we consider the problem of Lion and Man in the sense of L-capture, i.e. hit some neighborhood in the presence of a circular obstacle. A structure is proposed for constructing piecewise-constant pursuit controls that ensure the completion of the game in a finite time. A top estimate of the time of the game to complete the pursuit.